Crossing home – school border as rites de passage - Mendel, Maria (International Journal about Parents in Education, 2023)
We can analyse home – school discourse in accordance to Arnold van Gennep’s theory of the rites de passage (Van Gennep, 1986). Its essential three components (rites) might be perceived in the process of children’s and parents’ home – school transitions. Assuming that children and their parents transit from one to another social status quo we can see the basis for ritual forms of transition that are typical in such processes.We can also indicate binary oppositions that describe these statuses, e.g.: child vs. student, parent vs. parent of student. Thus, after van Gennep, we are able to name the following rites: rite of exclusion, rite de marge (marginalisation), and rite of inclusion in the home - school transition.The paper presents selected landscapes of school life, in which ritual pattern of transition (rittes de passage) are indicated and analysed in the context of potential opportunities of changes in the ways of parental involvement and democratisation of social life in Poland.